2018
DOI: 10.3390/md16040122
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Investigations on the Sea Urchin Tripneustes gratilla (Toxopneustidae, Echinoid) from Anaho Bay (Nuku Hiva, French Polynesia): Evidence for the Presence of Pacific Ciguatoxins

Abstract: The sea urchin Tripneustes gratilla (Toxopneustidae, Echinoids) is a source of protein for many islanders in the Indo-West Pacific. It was previously reported to occasionally cause ciguatera-like poisoning; however, the exact nature of the causative agent was not confirmed. In April and July 2015, ciguatera poisonings were reported following the consumption of T. gratilla in Anaho Bay (Nuku Hiva Island, Marquesas archipelago, French Polynesia). Patient symptomatology was recorded and sea urchin samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 66 publications
3
46
0
Order By: Relevance
“…blooms can provide baseline knowledge on the factors likely to influence fish ciguatoxicity in ciguatera-prone areas, and are therefore useful to inform CP risk models. The species G. polynesiensis is regarded as the dominant producer of CTXs in the food webs in French Polynesian lagoons [73]. The aim of the present study was to assess the overall toxin production and to characterize the toxin profiles in four strains of G. polynesiensis from distinct localities in French Polynesia, in relation to their growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…blooms can provide baseline knowledge on the factors likely to influence fish ciguatoxicity in ciguatera-prone areas, and are therefore useful to inform CP risk models. The species G. polynesiensis is regarded as the dominant producer of CTXs in the food webs in French Polynesian lagoons [73]. The aim of the present study was to assess the overall toxin production and to characterize the toxin profiles in four strains of G. polynesiensis from distinct localities in French Polynesia, in relation to their growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…g −1 ) than many of the fish species. Ciguatoxin occurrence in invertebrate species has been reported in other studies from the Pacific Islands [39,40], where they have been involved in ciguatera poisoning incidents [41]. However, they have not yet been included on any list of species of concern in the affected countries [42].…”
Section: Discussionmentioning
confidence: 99%
“…Here, LC-MS/MS data indicated that P-CTX3B and P-CTX3C, present in almost similar proportions (assuming the same response factor in LC-MS/MS for P-CTX3B and P-CTX3C), were the only known analogs detected in all tissue samples, even though the potential presence of other CTX congeners at concentrations below the limit of detection of the technique cannot be completely ruled out. Interestingly, P-CTX3B and P-CTX3C were also among the major congeners detected in Tectus niloticus (Gastropod) and Tripneustes gratilla (Echinoid) specimens involved in CFP poisoning events in French Polynesia [ 13 , 14 ], suggesting that both congeners are preferentially bio-accumulated by marine invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with field studies conducted on other marine invertebrates species also involved in CFP poisoning events in French Polynesia, which indicated that Tectus niloticus (Gastropod) and Tripneustes gratilla (Echinoid) have a slow detoxification rate for CTXs. Indeed, based on CBA-N2a results, a 19-fold and 64-fold decrease in the overall ciguatoxicity of Tectus niloticus and Tripneustes gratilla samples, respectively, was observed over a two-year period, but toxin concentrations were still consistently above the safety limit recommended for human consumption [ 13 , 14 ]. Of note, the authors also underlined that these findings may be confounded by the additional accumulation of CTXs over the study period, even in the presence of low cell numbers of Gambierdiscus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation